Analysis Of The Value Relevance Of Religiosity On Economic Behavior - Prasetyo, Deva; Bin Shuib , Mohd Sollehudin (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2023)
This study aims to determine the relevance of the value of religiosity to economic behavior by SAMIAJI rengginang producers. This research is descriptive research with a qualitative approach. The data collection technique used in this research is in the form of observations made at the SAMIAJI rengginang producer located in Warungasem, Batang. Then interviews with Mrs. Masruroh as the founder of the SAMIAJI business, and documentation techniques. The result of this research is that the SAMIAJI rengginang business, which is located in Warungasem Batang, has existed since 2013 with its founder, Mrs. Masruroh. This business produces three types of rengginang, namely jimpitan rengginang, small round rengginang and large rengginang. The production stages consist of steaming, printing, drying, frying and packaging stages. The religious values that are believed by the rengginang producers are honesty, trust, justice, responsibility and usefulness. Its relevance to production economic activities is that the existence of these religious values as moral and ethical shapers in production, so that production is more directed, clean and healthy. Such production can be beneficial for business continuity, because it can improve product quality and consumer loyalty.